Znajomość frazeologii regionalnej wśród poznaniaków - Kołodziejczyk, Marta (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The article discusses the issues related to the knowledge of the regional phraseology among present-day users of the local Poznań dialect. The research material is excerpted from a survey conducted among 120 local inhabitants within the age bracket of 15-87. Based on the results of the survey it is fair to conclude that the level of usage of the discussed phaseological units is highly dependent on the age of respondents, with the group of middle-aged people having the highest competence in the usage of dialectal forms. The most widely used expressions and phrases include those that describe the properties of human beings – physical and mental features and one’s behaviour or activities. The examination of the collected material allows us to compare the frequency within particular groups of phraseologisms that can be distinguished in the local dialect. It turns out that the most stable word groups are those units that have their counterparts in standard Polish, whereas the least stable are loan translations and the paraphrases from the German language. The article also indicates the similarities between the semantic structure of the phrasological layer in Poznań dialect and the structure of Polish colloquial vocabulary.
The knowledge of the local phraseology among the inhabitants of Poznań
Keywords: Frazeologizm; Regionalizm; Gwara miejska